2017
DOI: 10.4103/0259-1162.186607
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and pitfalls of cadavers as learning tool for ultrasound-guided regional anesthesia

Abstract: Ultrasound-guided regional anesthesia (UGRA), like other basic skills, should be learnt in a simulation laboratory before performing on the patient. Cadavers provide an ideal tool for learning sonoanatomy and skills required for performing UGRA. On the basis of preservation technique used, the cadavers can be formalin embalmed cadavers, Thiel cadavers (soft cadavers), and fresh frozen cadavers. We compared three types of cadavers for performing ultrasound-guided upper and lower limb blocks. We observed that fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…In addition, MDC values for the SL dimensions, such as length (MDC US = 0.069 cm versus MDC Caliper = 0.083 cm), thickness (MDC US = 0 cm versus MDC Caliper = 0.021 cm) and width (MDC US = 0.013 cm versus MDC Caliper = 0 cm), showed that US measurements presented a higher absolute accuracy with lower MDC values than caliper measures for SL length and thickness dimensions, while caliper displayed greater absolute accuracy with lower MDC for SL width dimensions. According to MDC may be used as the change magnitude necessary to provide measuring confidence to be sure about these values are not the result secondary random variations or measurement errors 12 , these MDCs may be considered as cut-off reference values to determine SL dimensions modifications secondary to anatomic abnormalities 58 , ultrasound-guided invasive procedures 9 , and ligament injuries course after treatment 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, MDC values for the SL dimensions, such as length (MDC US = 0.069 cm versus MDC Caliper = 0.083 cm), thickness (MDC US = 0 cm versus MDC Caliper = 0.021 cm) and width (MDC US = 0.013 cm versus MDC Caliper = 0 cm), showed that US measurements presented a higher absolute accuracy with lower MDC values than caliper measures for SL length and thickness dimensions, while caliper displayed greater absolute accuracy with lower MDC for SL width dimensions. According to MDC may be used as the change magnitude necessary to provide measuring confidence to be sure about these values are not the result secondary random variations or measurement errors 12 , these MDCs may be considered as cut-off reference values to determine SL dimensions modifications secondary to anatomic abnormalities 58 , ultrasound-guided invasive procedures 9 , and ligament injuries course after treatment 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-two feet from formaldehyde-embalmed human cadavers, 8 males and 26 females, without presence of any type of trauma were recruited in our research protocol 9 . The mean (SD) age was 76.46 (6.46) years; range from 66 to 89 years old.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, cadaver tissue often appears different from and lacks the respiratory variations of live human tissue with ultrasound imaging; thus, a cadaver model may not accurately reflect the performance of CDI in confirming ETT placement in live humans. 12,13 In this pilot study, we used video captured from live humans, with either tracheal or esophageal intubations, to evaluate whether CDI can improve correct ETT localization compared to grayscale US using an online assessment of medical professionals. We also investigated whether there is a relationship between the accuracy of US interpretation for this indication and the training level of participants.…”
Section: How Does This Improve Population Health?mentioning
confidence: 99%
“… 11 However, cadaver tissue often appears different from and lacks the respiratory variations of live human tissue with ultrasound imaging; thus, a cadaver model may not accurately reflect the performance of CDI in confirming ETT placement in live humans. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%